PERSEPSI MAHASISWA AKUNTANSI TERHADAP KEMAMPUAN DALAM MENDIRIKAN UMKM DAN MENYUSUN LAPORAN KEUANGAN - Leunupun, Engrith Grafelia; Killay, Thimotina (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
This study aims to understand students' perceptions regarding their desire to establish micro, small, and medium enterprises (UMKM) and the extent of their knowledge in preparing financial statements. This research is a qualitative study, using interviews and documentation as data collection techniques. The informants in this study are accounting students from the PSDKU MBD program. The results of the study indicate that although accounting students have a positive perception of their ability to establish UMKM, there are deficiencies in their practical knowledge of preparing financial statements in accordance with standards. This study suggests the importance of strengthening the curriculum to integrate accounting theory and practical applications in establishing and managing UMKM.